UMPSA Researchers help develop IoT System to boost oyster mushroom production - Mohammad Ilzam, Jamat (UMPSA, 2024)
BATU PAHAT, 30 September 2024 – A collaborative effort between Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and Ada Fresh Farm has successfully led to the development of a high-tech mushroom house equipped with an Internet of Things (IoT) system, representing a significant advancement in the agricultural industry, particularly in mushroom cultivation.